A dual-phase electrolyte for synergistically regulating a double electrode interface, a preparation method thereof and a zinc-manganese battery
Patent Information
- Application Number
- CN202610733205.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-26
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2046-05-26
AI Technical Summary
[0005]然而,现有双相电解液主要依赖双相结构实现物理隔离,尚未公开通过两亲锌盐在双相体系中的限域分布和原位转化,同时实现锌负极界面保护与正极侧 pH 稳定的技术方案
[0031] 1) This invention constructs a spontaneously stratified two-phase electrolyte system through the salting-out effect. The preparation method is simple and does not require the use of expensive ion exchange membranes. While simplifying the battery structure and reducing costs, it achieves synergistic regulation of the chemistry at the interface between the positive and negative electrodes, maintains a high discharge voltage platform, and improves the coulombic efficiency and cycle life of the battery.
Smart Images

Figure CN122267325B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, specifically to a two-phase electrolyte capable of simultaneously regulating the interfacial chemistry of the zinc anode and manganese dioxide cathode to achieve high voltage and long cycle stability, and a zinc-manganese battery containing the electrolyte. Background Technology
[0002] Against the backdrop of global energy transition, green, low-carbon, and sustainable development have become the themes of our time. With the rapid development of green and renewable energy sources such as wind, solar, and hydropower, not only has the entire energy system improved, but technological progress in modern society has also been promoted. However, the utilization of these energy sources is limited by geographical location and climate change, making it impossible to provide energy continuously and stably. Therefore, developing high-energy-density, stable, large-scale energy storage systems is particularly important. Currently, lithium-ion batteries, with their complete industrial chain and mature technology, are the main players in the energy storage battery market. Their high energy density and long cycle life have led to their widespread application in portable electronic devices and electric vehicles. However, safety issues remain a persistent problem for lithium-ion batteries. Therefore, developing safe and inexpensive zinc-ion batteries is crucial for the upgrading of the energy storage industry.
[0003] Currently, zinc-ion batteries are considered a candidate material for next-generation clean energy storage due to their high theoretical specific capacity (820 mAh g⁻¹). -1 Or 5855 mAh cm -3 MnO2, with its low redox potential (-0.762 V vs SHE), high zinc reserves, low cost, and safety and non-toxicity, is attracting increasing attention. Among these, MnO2 / Mn... 2+ Zinc-manganese batteries with a two-electron conversion reaction have a higher theoretical capacity (616 mAh g⁻¹). -1 ) and voltage plateau (1.99 V vs. Zn 2+ The system has attracted much attention due to its reliance on an acidic environment to ensure the deep reversibility of MnO2 conversion. However, this necessary condition triggers severe corrosion and hydrogen evolution side reactions in the zinc anode, leading to a sharp reduction in battery cycle life.
[0004] To address these contradictions, researchers have undertaken extensive work. Regarding electrolyte partitioning, the Hu Wenbin research group at Tianjin University reported in *Nature Energy*, 2020, 5: 440-449, that by placing an ion exchange membrane inside the battery to physically isolate the acidic positive electrode electrolyte from the neutral negative electrode electrolyte, the corrosion problem of the zinc negative electrode can be alleviated to some extent. However, this approach requires expensive ion exchange membrane materials and significantly increases the complexity of the battery structure, leading to a substantial increase in manufacturing costs and making it difficult to meet the needs of large-scale commercial applications. Regarding pH control, the Oliver Fitz team at the Fraunhofer Institute for Solar Energy Systems in Germany reported in *Energy Technology*, 2023, 11: 2300723, that by adding pH buffers such as acetic acid / acetate to the electrolyte, the H+ in the positive electrode region can be stabilized. + Concentration, increasing MnO2 / Mn 2+ The conversion of the redox couple is reversible. However, such buffers reduce the redox potential of MnO2, leading to a decrease in the energy density of the battery system, making it impossible to simultaneously meet the dual requirements of high energy density and long cycle life. Regarding anode protection, the team led by Zhao Xiangyu at Nanjing University of Technology reported in Advanced Materials, 2025, 37: e1432, that isoquinoline, as an interfacial adsorption additive, can inhibit the hydrogen evolution reaction on the zinc anode surface and improve anode stability. However, single-function additives can only improve anode performance and cannot simultaneously solve the problem of synergistic regulation of pH fluctuations on the cathode side and high-voltage conversion of MnO2, making it difficult to fundamentally overcome the performance bottleneck of existing zinc-manganese batteries. Recently, the team led by Kang Feiyu at Tsinghua University reported in J. Am. Chem. Soc, 2025, 147, 2714-2725, a two-phase electrolyte based on the Hofmeister effect, which separates the zinc anode from the aqueous phase of the bulk solution through phase separation, initially alleviating the problem of zinc anode corrosion under acidic conditions.
[0005] However, existing biphase electrolytes mainly rely on the biphase structure for physical isolation, and no technical solution has been disclosed that simultaneously achieves zinc anode interface protection and positive electrode pH stability through the confined distribution and in-situ transformation of amphiphilic zinc salts in the biphase system. In particular, existing technologies have not proposed utilizing amphiphilic zinc salts such as zinc tetrafluoroborate as functional electrolyte components, enabling them to participate in the formation of a ZnF2-rich interface layer on the zinc anode surface, and simultaneously through F… - The / HF buffering effect stabilizes the acidic environment of the positive electrode, thereby simultaneously improving the stability of the zinc negative electrode and the MnO2 / Mn ratio without using an ion exchange membrane to avoid the voltage plateau drop caused by conventional pH buffers. 2+ Transformation reversibility.
[0006] In summary, existing technologies still struggle to simultaneously achieve acidic MnO2 / Mn in a simple, low-cost battery structure. 2 + Positive electrode reaction, zinc negative electrode interface protection, and high-voltage stable output are all crucial aspects. Therefore, developing a two-phase electrolyte that can synergistically regulate the positive and negative electrode interfaces through electrolyte composition and phase structure design is of great significance for improving the cycle life, coulombic efficiency, and energy output of zinc-manganese batteries. Summary of the Invention
[0007] To address the shortcomings and drawbacks of the existing technology, the first objective of this invention is to provide a biphase electrolyte with synergistic regulation of the dual-electrode interface. This electrolyte utilizes the salting-out effect principle to construct a biphase electrolyte with spontaneous stratification of the organic / solution aqueous phase layer.
[0008] The second objective of this invention is to provide a method for preparing the above-mentioned biphase electrolyte with synergistic regulation of the dual electrode interface.
[0009] The third objective of this invention is to provide a zinc-manganese battery that uses a biphase electrolyte, allowing the zinc anode to be situated in a lean aqueous organic phase. Simultaneously, the in-situ hydrolysis of amphiphilic zinc salts achieves both interface protection of the zinc anode and pH stability on the cathode side. This eliminates the need for expensive ion exchange membranes and does not lower the battery's discharge voltage plateau. It achieves a simple and low-cost battery structure while simultaneously addressing acidic MnO2 / M ... 2+ Positive electrode reaction, zinc negative electrode interface protection, and high voltage stable output effectively improve the coulombic efficiency, cycle life, and energy density of zinc-manganese batteries.
[0010] Therefore, the first technical solution provided by this invention is as follows:
[0011] A biphase electrolyte for synergistic regulation of the dual-electrode interface comprises an inorganic acid, a hydrophilic salt, deionized water, a polar organic solvent, and an amphiphilic zinc salt; wherein the concentration of the amphiphilic zinc salt is 0.4~0.8 mol / L; and the concentration of the inorganic acid is 0.05~0.2 mol / L.
[0012] The amphiphilic zinc salt is one or a combination of zinc tetrafluoroborate and zinc bis(trifluoromethylsulfonyl)imide;
[0013] The hydrophilic salt is a combination of manganese sulfate and zinc sulfate.
[0014] Furthermore, the aforementioned biphase electrolyte with synergistic regulation of the dual-electrode interface includes an upper and lower layered aqueous solution and an organic solution. The aqueous solution includes an inorganic acid, deionized water, and a hydrophilic salt; the organic solution includes a polar organic solvent and an amphiphilic zinc salt.
[0015] The amphiphilic zinc salt described in this application undergoes in-situ hydrolysis during electrolyte circulation, and the F produced by hydrolysis... - It participates in the formation of a solid electrolyte interface film on the zinc anode surface and interacts with H. + A pH buffer pair is formed to stabilize the pH value on the positive electrode side.
[0016] Furthermore, the volume ratio of the organic phase layer to the aqueous phase layer in the solution is 1:1 to 1:3.
[0017] Furthermore, in the aforementioned biphase electrolyte with synergistic regulation of the dual-electrode interface, the polar organic solvent is one or a combination of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, acetonitrile, and dimethyl sulfoxide.
[0018] Furthermore, in the aforementioned synergistically regulated biphase electrolyte at the dual electrode interface, the inorganic acid is one or a combination of hydrochloric acid, sulfuric acid, and nitric acid.
[0019] Furthermore, in the aforementioned synergistically regulated biphase electrolyte at the dual electrode interface, the concentration of the amphiphilic zinc salt is 0.5~0.6 mol / L.
[0020] Furthermore, in the aforementioned synergistically regulated biphase electrolyte at the dual electrode interface, the concentration of manganese sulfate is 1~2 mol / L and the concentration of zinc sulfate is 1~3 mol / L.
[0021] The second technical solution provided by this invention is the above-mentioned method for preparing a two-phase electrolyte with synergistic regulation of the dual-electrode interface, which includes the following steps in sequence:
[0022] 1) Dissolve the hydrophilic salt and inorganic acid in deionized water and stir until completely dissolved to obtain an aqueous phase layer of the solution;
[0023] 2) Dissolve the amphiphilic zinc salt in a polar organic solvent to obtain an organic phase layer in the solution;
[0024] 3) Slowly add the organic phase layer of the solution prepared in step 2) to the aqueous phase layer of the solution prepared in step 1), and after standing, the solution will spontaneously separate into two phases to obtain a biphase electrolyte.
[0025] The present invention also provides a zinc-manganese battery, comprising a zinc negative electrode, a positive electrode, and an electrolyte, wherein the electrolyte is a biphase electrolyte with synergistic regulation of the dual electrode interface as described in the first technical solution; the zinc negative electrode is placed in the organic phase layer of the biphase electrolyte solution; and the positive electrode is placed in the aqueous phase layer of the biphase electrolyte solution.
[0026] Furthermore, in the aforementioned zinc-manganese battery, the positive electrode is a conductive carbon current collector loaded with the active material manganese dioxide.
[0027] Furthermore, the conductive carbon current collector is one of carbon felt, carbon cloth, or carbon paper.
[0028] Furthermore, the zinc-manganese battery has an operating voltage of 0.5~2.4 V and a discharge voltage plateau of ≥1.78 V.
[0029] Furthermore, the operating voltage of the zinc-manganese battery is any value among 0.5 V, 0.8 V, 1.2 V, 1.8 V, 2.0 V, and 2.4 V.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1) This invention constructs a spontaneously stratified two-phase electrolyte system through the salting-out effect. The preparation method is simple and does not require the use of expensive ion exchange membranes. While simplifying the battery structure and reducing costs, it achieves synergistic regulation of the chemistry at the interface between the positive and negative electrodes, maintains a high discharge voltage platform, and improves the coulombic efficiency and cycle life of the battery.
[0032] 2) This invention places the zinc anode within the organic phase of the solution, effectively reducing direct contact between water molecules and the zinc anode, thus suppressing hydrogen evolution and corrosion side reactions at the source. Simultaneously, the amphiphilic zinc salt in the organic phase of the solution slowly hydrolyzes during circulation, releasing F... - Ions in situ constructed a ZnF2-rich organic / inorganic composite solid electrolyte interface film on the zinc anode surface. This interface film effectively blocked H2. + The corrosion is reduced, promoting uniform deposition and stripping of zinc, which significantly improves the cycle stability and corrosion resistance of the zinc anode.
[0033] 3) This invention utilizes F produced by the hydrolysis of amphiphilic zinc salts. - With H in the aqueous phase of the solution + Formation of HF / F - The pH buffer pair stabilizes the local acidic environment on the positive electrode side, effectively suppressing pH fluctuations during MnO2 deposition / dissolution. This not only promotes the deep conversion of MnO2 and improves the utilization rate of active materials, but also facilitates the uniform deposition of MnO2, reduces the formation of "dead manganese," and thus significantly improves the MnO2 / Mn ratio. 2+ The reversibility of the conversion reaction and the cycle life of the battery.
[0034] 4) The polar organic solvent in the biphase electrolyte of this invention can partially enter the aqueous phase of the solution and participate in the Mn reaction. 2+ The solvation structure lowers the energy barrier of the MnO2 deposition reaction, accelerates the reaction kinetics, thereby improving the rate performance of the battery and stabilizing the discharge voltage plateau above 1.78 V, avoiding the problem of voltage drop caused by conventional pH buffers. Attached Figure Description
[0035] Figure 1 The diagram shows the structure and synergistic regulation mechanism of the two-phase electrolyte zinc-manganese battery assembled in Application Example 1.
[0036] Figure 2 The images show the Raman spectra of the biphase electrolyte in Example 1 before and after mixing.
[0037] Figure 3 During the charging and discharging process, BF4 in the two phases of the two-phase electrolyte in Example 1 - The in-situ Raman spectrum.
[0038] Figure 4 The graph shows the electrochemical cycling performance of the zinc-manganese full battery assembled with the biphase electrolyte prepared in Example 1.
[0039] Figure 5 The graph shows the electrochemical cycling performance of the zinc-manganese full battery assembled with the biphase electrolyte prepared in Example 2.
[0040] Figure 6 The graph shows the electrochemical cycling performance of the zinc-manganese full battery assembled with the biphase electrolyte prepared in Example 3.
[0041] Figure 7 The graph shows the electrochemical cycling performance of the zinc-manganese full battery assembled with the biphase electrolyte prepared in Example 4.
[0042] Figure 8 The graph shows the electrochemical cycling performance of the zinc-manganese full battery assembled with the biphase electrolyte prepared in Example 5.
[0043] Figure 9 The graph shows the electrochemical cycling performance of the zinc-manganese full battery assembled with the biphase electrolyte prepared in Example 6.
[0044] Figure 10 The graph shows the electrochemical cycling performance of the zinc-manganese full battery assembled with the biphase electrolyte prepared in Example 7.
[0045] Figure 11 The graph shows the electrochemical cycling performance of the zinc-manganese full cell assembled from the single-phase aqueous solution layer prepared in Comparative Example 1.
[0046] Figure 12 The graph shows the electrochemical cycling performance of the zinc-manganese full cell assembled with the two-phase electrolyte prepared in Comparative Example 2.
[0047] Figure 13 The zinc symmetric cells assembled with the electrolytes of Example 1 and Comparative Example 2 were tested at a current density of 1 mA cm⁻¹. -2 The deposition capacity is 1 mAh cm⁻¹ -2Comparison of time-voltage curves under the given conditions.
[0048] Figure 14 Scanning electron microscope images and corresponding elemental distribution maps of zinc anodes assembled with the electrolytes of Example 1 and Comparative Example 2 after cycling.
[0049] Figure 15 A comparison graph showing the pH changes of the aqueous phase layer of the zinc-manganese full battery solution in Example 1 under different charge and discharge conditions. Detailed Implementation
[0050] The specific embodiments of the present invention will be further described below. It should be noted that these descriptions are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0051] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the experimental materials used in the following embodiments can be purchased through conventional commercial channels unless otherwise specified.
[0052] Example 1
[0053] This embodiment provides a biphase electrolyte with synergistic regulation of the dual-electrode interface, which is prepared through the following steps: 1) Weigh 1.69 g of manganese sulfate monohydrate and 5.74 g of zinc sulfate heptahydrate and dissolve them in 8 mL of 0.1 mol / L dilute sulfuric acid to obtain an aqueous phase layer of the solution; 2) Weigh 0.6 g of zinc tetrafluoroborate hydrate and dissolve it in 5 mL of N,N-dimethylacetamide to obtain the organic phase layer of the solution; 3) Slowly add the organic phase layer obtained in step 2) to the aqueous phase layer prepared in step 1), wherein the volume ratio of the organic phase layer to the aqueous phase layer is 1:2; allow to stand and separate to obtain a two-phase electrolyte, the structure of which is as follows: Figure 1 As shown.
[0054] The 0.1 mol / L dilute sulfuric acid was prepared by diluting conventional analytical grade concentrated sulfuric acid with deionized water, wherein the concentration of concentrated sulfuric acid was 98 wt.%.
[0055] Example 2
[0056] The difference from Example 1 is that N,N-dimethylacetamide was replaced with an equal volume of N,N-dimethylformamide, while the other conditions were the same as in Example 1.
[0057] Example 3
[0058] The difference from Example 1 is that in step 1), 3.38 g of manganese sulfate monohydrate and 5.74 g of zinc sulfate heptahydrate were weighed and dissolved in 8 mL of 0.1 mol / L dilute sulfuric acid to obtain an aqueous phase layer. Other conditions were the same as in Example 1.
[0059] Example 4
[0060] The difference from Example 1 is that in step 1), 3.38 g of manganese sulfate monohydrate and 2.87 g of zinc sulfate heptahydrate were weighed and dissolved in 8 mL of 0.1 mol / L dilute sulfuric acid to obtain an aqueous phase layer. Other conditions were the same as in Example 1.
[0061] Example 5
[0062] The difference from Example 1 is that in step 1), 1.69 g of manganese sulfate monohydrate and 2.87 g of zinc sulfate heptahydrate were weighed and dissolved in 8 mL of 0.1 mol / L dilute sulfuric acid to obtain an aqueous phase layer. Other conditions were the same as in Example 1.
[0063] Example 6
[0064] The difference from Example 1 is that: in step 1), 1.69 g of manganese sulfate monohydrate and 5.74 g of zinc sulfate heptahydrate were weighed and dissolved in 8 mL of 0.05 mol / L dilute sulfuric acid to obtain an aqueous phase layer; other conditions were the same as in Example 1.
[0065] Example 7
[0066] The difference from Example 1 is that: in step 1), 1.69 g of manganese sulfate monohydrate and 5.74 g of zinc sulfate heptahydrate were weighed and dissolved in 8 mL of 0.2 mol / L dilute sulfuric acid to obtain an aqueous phase layer; other conditions were the same as in Example 1.
[0067] Example 8
[0068] The difference from Example 1 is that in step 2), 1.2 g of zinc tetrafluoroborate hydrate was weighed and dissolved in 5 mL of N,N-dimethylacetamide to obtain an organic phase layer in the solution; other conditions were the same as in Example 1.
[0069] Example 9
[0070] The difference from Example 1 is that in step 2), 0.8 g of zinc tetrafluoroborate hydrate was weighed and dissolved in 5 mL of N-methylpyrrolidone to obtain an organic phase layer in the solution; other conditions were the same as in Example 1.
[0071] Example 10
[0072] The difference from Example 1 is that: in step 2), 0.86 g of zinc bis(trifluoromethanesulfonyl)imide was weighed and dissolved in 5 mL of N-methylpyrrolidone to obtain an organic phase layer in the solution; other conditions were the same as in Example 1.
[0073] Example 11
[0074] The difference from Example 1 is that the organic phase layer and the aqueous phase layer in step 3) are in a volume ratio of 1:1; other conditions are the same as in Example 1.
[0075] Example 12
[0076] The difference from Example 1 is that the volume ratio of the organic phase layer and the aqueous phase layer in step 3) is 1:3; other conditions are the same as in Example 1.
[0077] Comparative Example 1
[0078] The difference from Example 1 is that the electrolyte uses only the aqueous phase layer of the solution in Example 1 (i.e., no organic phase layer is added).
[0079] Comparative Example 2
[0080] The difference from Example 1 is that zinc tetrafluoroborate is not added to the organic phase of the solution, while the other conditions are the same as in Example 1.
[0081] Comparative Example 3
[0082] The difference from Example 1 is that dilute sulfuric acid is not added to the aqueous phase of the solution, while the other conditions are the same as in Example 1.
[0083] Application Example 1
[0084] This application example provides a zinc-manganese battery. The biphase electrolyte prepared in Example 1 is used as the electrolyte, zinc foil is used as the negative electrode, and electrodeposited MnO2 carbon felt is used as the positive electrode, assembled into a mold battery. The effective area of both the positive and negative electrodes is 1 cm². 2 Furthermore, the negative electrode is placed in the organic phase layer of the biphase electrolyte solution; the positive electrode is placed in the aqueous phase layer of the biphase electrolyte solution.
[0085] Charge / discharge conditions: Charge at a constant voltage to a certain areal capacity (0.5 mAh cm⁻¹). -2 Then, constant current discharge is applied, with a constant charging voltage of 2.0 V and a discharge current density of 0.5 mA cm⁻¹. -2 The discharge cutoff voltage is 0.8 V.
[0086] Application Example 2-12
[0087] Application Example 2-12 provides a zinc-manganese battery in which the biphase electrolyte prepared in any of Examples 2-12 is used instead of the biphase electrolyte prepared in Example 1. The specific correspondence is shown in Table 1.
[0088] Comparative Application Examples 1-3
[0089] Comparative Application Examples 1-3 provide a zinc-manganese battery in which the electrolyte prepared in any of Comparative Examples 1-3 is used instead of the biphase electrolyte prepared in Example 1. The specific correspondence is shown in Table 1.
[0090] Table 1
[0091] Application Example 1 The biphase electrolyte prepared in Example 1 Application Example 2 The biphase electrolyte prepared in Example 2 Application Example 3 The biphase electrolyte prepared in Example 3 Application Example 4 The biphase electrolyte prepared in Example 4 Application Example 5 The biphase electrolyte prepared in Example 5 Application Example 6 The biphase electrolyte prepared in Example 6 Application Example 7 The biphase electrolyte prepared in Example 7 Application Example 8 The biphase electrolyte prepared in Example 8 Application Example 9 The biphase electrolyte prepared in Example 9 Application Example 10 The biphase electrolyte prepared in Example 10 Application Example 11 The biphase electrolyte prepared in Example 11 Application Example 12 The biphase electrolyte prepared in Example 12 Comparative Application Example 1 Electrolyte prepared in Comparative Example 1 Comparative Application Example 2 Electrolyte prepared in Comparative Example 2 Comparative Application Example 3 Electrolyte prepared in Comparative Example 3
[0092] To more clearly illustrate the effect of the biphase electrolyte of the present invention on the regulation of the performance of the two-electrode interface, the performance of the present invention is characterized in detail below with reference to test examples.
[0093] Test Example 1: Electrolyte Composition Characterization
[0094] The composition of the electrolyte was analyzed using a fully automated Raman spectrometer.
[0095] The Raman spectra of the organic phase and aqueous phase of the solution before and after electrolyte mixing in Example 1 are shown below. Figure 2 .from Figure 2 The results show that the organic phase of the mixed solution has an additional water peak, indicating that some water is miscible with N,N-dimethylacetamide; BF4 was not detected in the aqueous phase of the mixed solution. - This indicates that BF4 - It was confined to the organic phase of the solution. The aqueous phase of the solution contained two additional characteristic peaks corresponding to N,N-dimethylacetamide, indicating that the aqueous phase of the solution contained a small amount of N,N-dimethylacetamide.
[0096] For the structure of the assembled cuvette cell for in-situ Raman testing, please refer to [link / reference]. Figure 3 .from Figure 3 As can be seen from this, during the charging and discharging process, BF4 in the organic phase layer of the solution... - The peak intensity and position remained almost unchanged. Furthermore, BF4 was not observed in the in-situ Raman spectrum of the aqueous solution layer. - Characteristic peaks. Therefore, during the cycling process, BF4 - It is confined within the organic phase layer of the solution.
[0097] Test Example 2: Performance Test of Zinc-Manganese Full Cell
[0098] Electrochemical cycle performance tests were conducted on the zinc-manganese full cells assembled according to the corresponding use cases 1-7 and the comparative application examples 1-3.
[0099] Examples 1-7 and Comparative Examples 2-3 used a two-phase electrolyte, with the negative electrode placed in the organic phase layer and the positive electrode placed in the aqueous phase layer. Comparative Example 1 used a single-phase electrolyte, with both the positive and negative electrodes placed in the single-phase electrolyte. The charging cutoff voltage was 2.0 V, the discharging cutoff voltage was 0.8 V, and the current density was 0.5 mA cm⁻¹. -2 Constant current charge-discharge performance was tested under the specified conditions, and the test results are shown in Table 2. The electrochemical cycle performance graph is referenced. Figures 4 to 12 .
[0100] Table 2 Electrochemical performance of Examples 1-7 and Comparative Examples 1-3
[0101] Application Example 1 1.85 98.7 0.485 400 Application Example 2 1.82 92 0.45 79 Application Example 3 1.80 93 0.43 96 Application Example 4 1.79 94 0.42 200 Application Example 5 1.78 95 0.42 75 Application Example 6 1.78 96 0.44 120 Application Example 7 1.83 95 0.42 159 Comparative Application Example 1 1.85 90 0.41 100 Comparative Application Example 2 1.68 95 0.46 50 Comparative Application Example 3 1.66 90 0.4 110
[0102] From Table 2, Figures 4-12 It can be known that:
[0103] Application Example 1 exhibits the best overall electrochemical performance, with a discharge voltage plateau of 1.85 V, an average coulombic efficiency of 98.7%, and a discharge surface capacity of 0.485 mAh cm⁻¹. -2 The cycle life reached 400 cycles. In contrast, Comparative Example 1 used a single-phase aqueous solution layer. Although the discharge voltage plateau was also 1.85 V, the average coulombic efficiency decreased to 90%, and the discharge surface capacity was 0.41 mAh cm⁻¹. -2 The cycle life is only 100 cycles, indicating that the biphase electrolyte can effectively reduce side reactions such as corrosion and hydrogen evolution by separating the zinc anode from the aqueous phase of the acidic solution, thereby significantly improving cycle stability.
[0104] When the electrolytes in Application Examples 6 and 7 were 0.05 mol / L and 0.2 mol / L sulfuric acid, respectively, the discharge voltage plateaus were 1.78 V and 1.83 V, and the cycle lives were 120 cycles and 159 cycles, respectively, both lower than those in Application Example 1. This indicates that both excessively low and excessively high sulfuric acid concentrations will have an adverse effect on the stability of the system, and 0.1 mol / L is more suitable.
[0105] After adjusting the concentration combinations of manganese sulfate and zinc sulfate in the electrolytes of Application Examples 3 to 5, the cycle lives were 96, 200, and 75 cycles, respectively. Overall, they still did not exceed those of Application Example 1, indicating that the salt concentration combination of 2 mol / L zinc sulfate and 1 mol / L manganese sulfate is more conducive to obtaining better overall performance.
[0106] In Application Example 2, after replacing N,N-dimethylacetamide with N,N-dimethylformamide in the electrolyte, the discharge voltage plateau was 1.82 V, the average coulombic efficiency was 92%, and the cycle life decreased to 79 cycles, indicating that N,N-dimethylacetamide is more suitable as a polar organic solvent in this two-phase system.
[0107] Compared to the electrolyte in Application Example 2, which, without the addition of Zn(BF4)2, still uses a two-phase electrolyte, its discharge voltage plateau drops to 1.68 V, the average coulombic efficiency is 95%, and the cycle life is only 50 cycles, which is significantly worse than Application Example 1. This indicates that relying solely on the physical isolation provided by the two-phase electrolyte is insufficient to achieve stable battery cycling. Zn(BF4)2 plays a crucial role in protecting the zinc anode, stabilizing the pH of the cathode, and maintaining a high discharge voltage plateau.
[0108] Compared to the electrolyte in Application Example 3, which, without the addition of inorganic acid to the aqueous phase of the solution, still employs a two-phase electrolyte structure containing Zn(BF4)2, its discharge voltage plateau is only 1.70 V, its average coulombic efficiency is 90%, and its discharge surface capacity is 0.40 mAh cm⁻¹. -2 The number of cycles is 100, which is lower than that of Application Example 1.
[0109] This result demonstrates that, in the MnO2 / Mn of the present invention 2+ In conversion-type zinc-manganese battery systems, inorganic acids are key components for regulating the cathode reaction environment and improving electrochemical stability. An appropriate amount of inorganic acid can enhance the MnO2 / Mn... 2+ The conversion reaction provides the necessary acidic conditions, and is associated with the confined hydrolysis of Zn(BF4)2 in the organic phase of the solution and F - The / HF buffer works synergistically to maintain the stability of the acidic environment on the positive electrode side.
[0110] Test Example 3: Zinc Anode Interface Characterization and Symmetric Cell Performance
[0111] Take the two-phase electrolyte from Application Example 1 after it has been allowed to separate into layers. Take 120 μL of electrolyte from the organic phase layer of the upper solution. Use two zinc foils as the working electrode and the counter electrode, respectively. Assemble a Zn / / Zn symmetrical cell using a CR2032 coin cell and a Whatman glass fiber membrane as the separator. For comparison, a symmetrical cell was assembled using a 0.5 M Zn(BF4)2 aqueous solution as the electrolyte, following the same method. The current density was 1 mA cm⁻¹. -2 The deposition capacity is 1 mAh cm⁻¹ -2 A constant current charge-discharge test was performed under the specified conditions. The time-voltage curve is shown below. Figure 13As shown, the battery prepared in Application Example 1 has stable cycling for more than 650 hours with stable polarization voltage; while the symmetric battery assembled with 0.5 M Zn(BF4)2 aqueous solution experienced short-circuit failure after about 17 hours of cycling.
[0112] Scanning electron microscope images and corresponding elemental distributions are as follows: Figure 14 As shown. In Example 1, the surface of the zinc foil after circulation in the organic phase layer of the solution is smooth and flat, and the F element is evenly distributed, indicating that a uniform fluorine-containing interface layer has been formed.
[0113] Test Example 4: Characterization of pH stability on the positive electrode side
[0114] During the cycling of the zinc-manganese full battery in Application Example 1 and Comparative Application Example 2, the pH value changes of the aqueous phase layer in the electrolyte were monitored. Figure 15 The pH values of the aqueous phase layer of the solution under different charge and discharge states are shown. In contrast, the pH value of the electrolyte in Application Example 2 fluctuates significantly with charge and discharge states, while the pH value of the two-phase electrolyte in Application Example 1 changes much less, indicating that the HF / F ratio in Example 1... - The buffer pair plays a role in stabilizing the pH.
[0115] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.
Claims
1. A bi-phasic electrolyte for synergistically modulating a double electrode interface, characterized in that, It includes inorganic acids, hydrophilic salts, deionized water, polar organic solvents, and amphiphilic zinc salts; the concentration of the amphiphilic zinc salts is 0.4~0.8 mol / L; the concentration of the inorganic acids is 0.05~0.2 mol / L; The amphiphilic zinc salt is zinc tetrafluoroborate; The hydrophilic salt is a combination of manganese sulfate and zinc sulfate; The polar organic solvent is N,N-dimethylacetamide.
2. The biphase electrolyte with synergistic regulation of the dual-electrode interface according to claim 1, characterized in that, It includes an aqueous phase solution and an organic phase solution, which are separated into two layers. The aqueous phase solution includes an inorganic acid, deionized water, and a hydrophilic salt. The organic phase solution includes a polar organic solvent and an amphiphilic zinc salt.
3. The biphase electrolyte with synergistic regulation of the dual-electrode interface according to claim 1 or 2, characterized in that, The inorganic acid is one or any combination of hydrochloric acid, sulfuric acid, and nitric acid.
4. The biphase electrolyte with synergistic regulation of the dual-electrode interface according to claim 1 or 2, characterized in that, The concentration of the amphiphilic zinc salt is 0.5~0.6 mol / L.
5. The biphase electrolyte with synergistic regulation of the dual-electrode interface according to claim 1 or 2, characterized in that, The concentration of manganese sulfate is 1~2 mol / L and the concentration of zinc sulfate is 1~3 mol / L.
6. The biphase electrolyte with synergistic regulation of the dual-electrode interface according to claim 2, characterized in that, The volume ratio of the organic phase solution to the aqueous phase solution is 1:1 to 1:
3.
7. A method for preparing a biphase electrolyte with synergistically regulated dual-electrode interface as described in claim 1 or 2, characterized in that, The steps are as follows: 1) Dissolve the hydrophilic salt and inorganic acid in deionized water and stir until completely dissolved to obtain an aqueous phase solution; 2) Dissolve the amphiphilic zinc salt in a polar organic solvent to obtain an organic phase solution; 3) Slowly add the organic phase solution prepared in step 2) to the aqueous phase solution prepared in step 1), and after standing, the two-phase electrolyte will spontaneously separate into layers.
8. A zinc-manganese battery, characterized in that, The device includes a zinc foil negative electrode, a positive electrode, and an electrolyte, wherein the electrolyte is a two-phase electrolyte with synergistic regulation of the dual electrode interface as described in any one of claims 1-2; the zinc foil negative electrode is placed in the organic phase layer solution of the two-phase electrolyte; and the positive electrode is placed in the aqueous phase layer solution of the two-phase electrolyte.
9. The zinc-manganese battery according to claim 8, characterized in that, The positive electrode is a conductive carbon current collector loaded with the active substance manganese dioxide.